Knowledge, attitudes and personal beliefs about HIV and AIDS among mentally ill patients in Soweto, Johannesburg - G Jonsson; M Y H Moosa; F Y Jeenah (AOSIS, 2011)
Aim. The aim of the study was to determine knowledge, attitudes and personal beliefs regarding HIV and AIDS in a group of mentally ill patients attending outpatient clinics in Soweto, Johannesburg. Method. All patients attending four randomly chosen clinics in Soweto were invited to complete a self-administered questionnaire after obtaining informed written consent. The 63-item questionnaire, developed from others specifically for this study, included questions on socio-demographic and clinical characteristics; knowledge on how HIV is acquired and spread; attitudes and beliefs regarding HIV and AIDS; and condom usage. The statements in the knowledge sections were used to calculate a composite score, which if greater than or equal to 75% was defined as 'adequate knowledge'. Results. A total of 1 151 patients with mental illness participated in the study. The mean age was 41.9 years (standard deviation 11.6) and the majority were males (50%); single (55%), and had achieved only a secondary level of education (53.3%). Overall, most of the study population did not believe in the myths surrounding the spread and acquisition of HIV and AIDS. There were however, significant associations between a low level of education and the belief that HIV is acquired from mosquito bites (odds ratio (OR) 1.61; 95% CI 1.19 - 2.18; p=0.002) and through masturbation or body rubbing (OR 1.76; 95% CI 1.34 - 2.33; p=0.000). Although more than 90% of the patients were aware of the facts regarding the spread of HIV, approximately 40% did not believe that one could acquire HIV through a single sexual encounter. The composite scoring for knowledge showed that less than half the patients had adequate knowledge of HIV/AIDS. This was significantly associated with gender and level of education: females were 1.6 times (p